2003
DOI: 10.1038/sj.ijir.3901069
|View full text |Cite
|
Sign up to set email alerts
|

Update on central function relevant to sex: remodeling the basis of drug treatments for sex and the brain

Abstract: Sexual function draws on a complex network of peripheral and central neural pathways. The standard focus on erectile difficulties and peripheral therapies has been highly successful clinically but there are many unresolved issues in men and newly discussed issues in women that will likely benefit from improved understanding of the central nervous system and sexual function. The spectrum of future therapies, based on evolving central neurophysiological understanding, will include the management of problems rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Natural rewards are highly controlled by feedback mechanisms, which may lead to a quicker return to “baseline” by promoting (for example) an aversion to engaging in the same rewarding activity immediately after the pleasant stimulation (Small, Zatorre, Dagher, Evans, and Jones-Gotman 2001). For example, the building-up of sexual desire often precedes a sexual act (e.g., Heaton and Adams 2003), after which it quickly decreases and then takes time to recover its initial level of intensity. Addictive stimulants, on the other hand, often rebuild high levels of desire immediately after drug consumption (e.g., Nestler 2005).…”
Section: What About Differences?mentioning
confidence: 99%
“…Natural rewards are highly controlled by feedback mechanisms, which may lead to a quicker return to “baseline” by promoting (for example) an aversion to engaging in the same rewarding activity immediately after the pleasant stimulation (Small, Zatorre, Dagher, Evans, and Jones-Gotman 2001). For example, the building-up of sexual desire often precedes a sexual act (e.g., Heaton and Adams 2003), after which it quickly decreases and then takes time to recover its initial level of intensity. Addictive stimulants, on the other hand, often rebuild high levels of desire immediately after drug consumption (e.g., Nestler 2005).…”
Section: What About Differences?mentioning
confidence: 99%
“…Many neurophysiological studies showed that both male and female urethrogenital reflex is controlled in part by the spinal cord, and by inhibitory and excitatory influence of supraspinal sites, including the nucleus paragigantocellularis, the paraventricular nucleus of the hypothalamus, and the medial preoptic area (e.g., Heaton & Adams, 2003;Holstege, 2005;Mah & Binik, 2001;McKenna, 1999;Rowland, 2006). Because there has been very little research on orgasm in female animals, no clear gender differences have been reported in animal models (Giuliano et al, 2001;McKenna, 1999;Meston et al, 2004).…”
Section: Gender Differences In Human Orgasmmentioning
confidence: 99%
“…(e.g., Bancroft et al, 2003;Basson, 2000;Heaton & Adams, 2003;Kaplan, 1974Kaplan, , 1979Mah & Binik, 2005;Masters & Johnson, 1966;Meston et al, 2004;Whipple & Brash-McGreer, 1997). By specifying the brain areas involved in these mechanisms, contemporary neuroimaging studies throw considerable light on brain activity related to woman's orgasm, as it has been done previously in men (such as Graber, Rohrbaugh, Newlin, Varner, & Ellingson, 1985;Heath, 1972;Heaton & Adams, 2003;Holstege, 2005;Holstege & Georgiardis, 2004;Holstege et al, 2003;McKenna, 1999;Mosovich & Tallaferro, 1954;Rowland, 2006;Tiihonen et al, 1994). This is of particular importance in the field of neuropsychology where patients who suffer from a brain injury may have impaired or affected orgasms.…”
Section: Functional Brain Imaging In Healthy Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of AP-SD remain largely unclear, and current theories derive mainly from studies of general sex physiology and psycho-pharmacology. The responses of various sexual components are under the control of numerous central and peripheral neural systems [7,8]. It has been postulated that a direct dopamine D2 receptor antagonist effect of antipsychotics may be the primary central mechanism, along with some indirect neuroendocrine factors, such as elevated prolactin levels [9].…”
mentioning
confidence: 99%